2012
DOI: 10.3109/0142159x.2012.735382
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring and role models in recruitment and retention: A study of junior medical faculty perceptions

Abstract: Purpose: This study explored the views of junior faculty toward informing mentorship program development. Method: Mixed sampling methodologies including questionnaires (n ¼ 175), focus groups (female, n ¼ 4; male, n ¼ 4), and individual interviews (female n ¼ 10; male, n ¼ 9) of junior faculty were conducted in clinical departments at one academic health sciences center. Results: Questionnaire results indicated that having role models increased commitment to an academic career; mentorship experience during res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 43 publications
2
65
0
4
Order By: Relevance
“…[1][2][3] Surveys of program directors of graduate medical education programs report the proportion of programs offering mentorship vary from 49% in US Internal Medicine programs 4 to 65% in Canadian postgraduate programs. 5 When mentoring programs are available, the mentoring activities are often loosely monitored and the outcomes poorly evaluated.…”
Section: Mentors Are Increasingly Recognized As Crucial Tomentioning
confidence: 98%
“…[1][2][3] Surveys of program directors of graduate medical education programs report the proportion of programs offering mentorship vary from 49% in US Internal Medicine programs 4 to 65% in Canadian postgraduate programs. 5 When mentoring programs are available, the mentoring activities are often loosely monitored and the outcomes poorly evaluated.…”
Section: Mentors Are Increasingly Recognized As Crucial Tomentioning
confidence: 98%
“…Early career researchers emphasised how important a research supervisor was to their academic career advancement. 21 57 58 Those who were based in an academic setting that nurtured supportive mentorship and positive role modelling tended to pursue academic medicine with greater career satisfaction and confidence. [59][60][61] Optimal mentorship was marked by altruistic guidance and clarity from supervisors who encouraged junior faculty.…”
Section: Type Of Literaturementioning
confidence: 99%
“…There is a wealth of literature exploring the influence of role models in many specialties, for example, Ravindra and Fitzgerald19 found a significant link between identifying a surgical role model and aspirations of a surgical career and Steele et al 20 identified how the presence of role models can encourage retention of doctors within academic medicine.…”
Section: Discussionmentioning
confidence: 99%